IGNATIEFF, Michael (2014). Fuego y cenizas. Éxito y fracaso en política. Madrid: Editorial Taurus (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2015)
Recensión de la obra: IGNATIEFF, Michael (2014). Fuego y cenizas. Éxito y fracaso en política. Madrid: Editorial Taurus.